Pengaruh Literasi Keuangan Syariah, Penggunaan Shopee Paylater dan Lifestyle Terhadap Perilaku Konsumtif: Studi Kasus pada Mahasiswa Program Studi Perbankan Syariah UMSU - Putri Ayu Lestari; Khairunnisa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted with the aim of finding out the influence of sharia financial literacy, use of shopee paylater, lifestyle on the consumptive behavior of students in the UMSU Sharia Banking Study Program. The type of approach used is quantitative with an associative type of research. The research population was 190 UMSU Sharia Banking Study Program students, while the sample used was 130 respondents who were the research sample. This research uses Purposive Sampling technique. The data used is primary data and the data collection technique uses a questionnaire via Google Form. The variables used are the independent variables in the form of financial literacy, use of Shopee Paylater and also Lifestyle, while the dependent variable is consumer behavior. The data analysis technique used in this research uses Multiple Linear Regression Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used SPSS (Statistical Package For The Social Sciences) version 29.00 (2024). Based on the research results, it shows that Sharia Financial Literacy has a positive but not significant influence on student consumptive behavior. Using Shopee Paylater has a positive and significant influence on student consumptive behavior. And Lifestyle has a positive and significant effect on student consumption behavior.